The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/aas.12505
|View full text |Cite
|
Sign up to set email alerts
|

A 10‐year retrospective study of interhospital patient transport using inhaled nitric oxide in Norway

Abstract: Transporting patients on inhaled nitric oxide is an alternative in selected patients who would otherwise require extracorporeal membrane oxygenation during transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Modern air ambulance services are able to provide advanced interventions during transport, including intensive care procedures, differentiated catecholamine therapy, volume resuscitation, modern ventilation strategies, ECMO, inhaled nitric oxide, or even the use of heart-assisted devices (e.g. like Impella®) during transport [ 12 15 ]. Several guidelines recommend the use of ECMO or inhaled nitric oxide in selected COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Modern air ambulance services are able to provide advanced interventions during transport, including intensive care procedures, differentiated catecholamine therapy, volume resuscitation, modern ventilation strategies, ECMO, inhaled nitric oxide, or even the use of heart-assisted devices (e.g. like Impella®) during transport [ 12 15 ]. Several guidelines recommend the use of ECMO or inhaled nitric oxide in selected COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Such transports aren’t “just transport”, but “bringing the university hospital closer to the patient”. The Air Ambulance department at Oslo University Hospital has an already well-established practice for both initiation of iNO treatment as well as providing continuous iNO treatment during the retrieval phase [13].…”
Section: Discussionmentioning
confidence: 99%
“…Power calculation. One previous study in a different setting has shown that 71% of patients respond to the treatment with an absolute increase in SpO 2 of >5 percentage points [23]. We assume a standard deviation of 10 percentage points, and a within subject correlation of 0.8 based on clinical experience.…”
Section: Discussionmentioning
confidence: 99%